2016
DOI: 10.3389/fphys.2016.00501
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Heart Rate in Non-linear HRV Indices as a Sampling Rate Effect Evaluated on Supine and Standing

Abstract: The purpose of this study is to characterize and attenuate the influence of mean heart rate (HR) on nonlinear heart rate variability (HRV) indices (correlation dimension, sample, and approximate entropy) as a consequence of being the HR the intrinsic sampling rate of HRV signal. This influence can notably alter nonlinear HRV indices and lead to biased information regarding autonomic nervous system (ANS) modulation. First, a simulation study was carried out to characterize the dependence of nonlinear HRV indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…This implies that a physiological correlation exists between HRV and HR. However, in a simulation study, it was demonstrated that the changes in the ANS modulation should be independent of the changes in the mean HR [7]. This is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…This implies that a physiological correlation exists between HRV and HR. However, in a simulation study, it was demonstrated that the changes in the ANS modulation should be independent of the changes in the mean HR [7]. This is consistent with the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…where ∆f is twice the resolution of Hamming window, ∆f = 2.6 Fs N , being F s the sampling frequency and N the number of samples of the window (50 seg ×4 samples/seg = 200 samples). The limits of [0.15-HR/2] Hz are imposed in order to ensure that no power from the LF band or from components with uncertain origin are considered (HR/2 Hz is the highest frequency we can represent in HRV spectrum, as HR is the intrinsic sampling frequency of HRV [34]).…”
Section: E Peaknessmentioning
confidence: 99%
“…2, the lower frequency bound of the classical band could be inadequate when some not welldefined components (mid-frequency band [33]) are present, as power with an origin distinct from parasympathetic activity will contaminate the HF band. In addition, the upper bound of 0.4 Hz could be not enough when respiratory rate is high as some HF power will leak out of the band (young children present high respiratory rates [38]), so HR/2 was considered as it is the highest representable frequency in HRV spectrum, due to the fact that HR is the intrinsic sampling frequency of HRV [34]. Table II show statistical significant differences between LoR and HiR in ℘ IP HRV , R LF/HF and P LFn , thus suggesting a peakier component in the HF band accompanied by a reduced sympathovagal balance in HiR.…”
Section: ℘ Ipmentioning
confidence: 99%
“…Sympathetic and parasympathetic regulations are related to the HRV content analyzed in low (0.04-0.15 Hz) and high (0.15-0.4 Hz) frequency bands, respectively, during relax conditions in adult healthy subjects 1 . Furthermore, nonlinear HRV assessment relates changes on sympathovagal balance to regularity and complexity of ANS 8 .…”
Section: Introductionmentioning
confidence: 99%